Formation of chelate structure between His-Met dipeptide and diaqua-cisplatin complex; DFT/PCM computational study - Maixner, Michal; Dos Santos, Helio F; Burda, Jaroslav V (Journal of biological inorganic chemistry, 2018)
Interaction of cisplatin in activated diaqua-form with His-Met dipeptide is explored using DFT approach with PCM model. First the conformation space of the dipeptide is explored to find the most stable structure (labeled 0683). Several functionals with double-zeta basis set are used for optimization and obtained order of conformers is confirmed by the CCSD(T) single-point calculations. Supermolecular model is used to determine reaction coordinate for the replacement of aqua ligands consequently by N-site of histidine and S-site of methionine and reversely. Despite the monoadduct of Pt-S(Met) is thermodynamically less stable this reaction passes substantially faster (by several orders of magnitude) than coordination of cisplatin to histidine. The consequent chelate formation occurs relatively fast with energy release up to 12 kcal mol-1.
Keywords: Kinetics; protinádorové látky; teorie funkcionálu hustoty; chelátory; Anticancer drug; Methionine; Histidine; methionin; cisplatina; termodynamika; dipeptidy; Density Functional Theory; histidin; Computational chemistry; Heavy metal; Cisplatin; Thermodynamics; kinetika; Dipeptides; Antineoplastic Agents; Chelating Agents; Density functional theory